Chronic fatigue syndrome - criteria for diagnosis, etiology, treatment - Pankanin, Ewelina Stefania (Journal of Education, Health and Sport, 2018)
Chronic fatigue syndrome is a disease that has been observed for a long time. It appeared under various names, often associated with the theory of the etiology of CFS - chronic fatigue syndrome. Despite many studies, the causes of chronic fatigue syndrome have not yet been defined. The consequence of this are difficulties in diagnosis and then in the treatment of this disease.